A narrativa sinalizada da criança surda : aspectos multimodais na interação em sala do AEE - Silva, Charlene de Lima Alexandre da (2024)
In this work, we discuss children's narratives produced by deaf children, with contributions from the Multifunctional Resource Room teacher. Our general objective was to analyze the elaboration of signed narratives and the interaction of a deaf child in Early Childhood Education V with the AEE teacher and its importance in this construction in a municipal school in Jaboatão dos Guararapes-PE. As specific objectives we propose to observe the resources that the deaf child uses to participate in the narrative; describe how the dyad intertwines: deaf child and AEE teacher; explore linguistic elements that are produced among deaf children; demonstrate how the AEE teacher plans to use resources and mediation strategies to use the narrative. In data collection, we used filming of the narrative inside the Specialized Educational Service room (SRM) with the Specialized Educational Service (AEE) teacher. As an instrument to achieve our objectives, the teacher who teaches classes in Brazilian Sign Language (Libras) during the deaf child's service hours does work focused on potty training. To support our work, we took as a reference the research of: Cavalcante (1994, 2009); Ávila-Nóbrega (2017); Quadros (2008); McNeill (1992, 1994, 2002); Kendon (1982); Quadros (2007, 2008); Skliar (1999, 1997); Lillo-Martin (2007), Volterra (2006), Sisto (2012), Busatto (2012), among others who were concerned with presenting to our society a new way of seeing deaf education, Libras, gestures, narratives and the linguistic elements present, so the authors in their specificities share a range of ideas, enabling studies aimed at a broad discussion about our topic. Our data were filmed with a 5 (five) year old deaf child, in the AEE room, consisting of 3 meeting sessions with a child, the researcher, the AEE teacher and the child's father as responsible for the filming lasting of 4 (four) minutes and 9 (nine) seconds. We postulate that the child in an interaction with the teacher presents interactions that are intertwined in the directed gaze, pointing sign with linguistic components present in Libra such as iconic signs and deictic signs, which are very present.